Avulsion of both posterior meniscal roots associated with acute rupture of the anterior cruciate ligament - Mariani, Pier Paolo (J Orthop Traumatol, 2014)
A rare case of acute avulsion of both posterior meniscal roots concomitant with an acute anterior cruciate ligament (ACL) tear in a professional soccer player is described. While avulsion of the lateral meniscal root has been extensively reported in association with ACL injuries, medial root avulsion has never been reported in association with acute ACL. A review of the video documentation of the match accident revealed the exact mechanism of injury was a forceful external rotation of the standing limb.